The tradition «Cortar por lo sano» and its relation to the dehumanization of Peruvian society - López Bocanegra, Carlos Alonso (2019)
This article will analyze the connection between the story «Cortar por lo sano» and the demoralization of the Peruvian society. It is proposed that in this text the narrator Ricardo Palma presents an allegory of the current Peruvian society and shows us how «rotten» people in our society, in other words, corrupted by hatred, dehumanized, try to understand and see things at their own convenience in order to take «advantage» of them, without previously considering the consequences that this may have on others. I will cover topics from politics and the government of the country, to cases of corruption, citizen insecurity and gender violence.